Pengaruh Outdoor Education Terhadap Peningkatan Kepercayaan Diri Siswa dalam Aspek Rasional dan Realistis: Sebuah Studi Eksperimen di SMP Yayasan Wanita Kereta Api Bandung - Suhendra, Dede Iman (Jurnal Keolahragaan, 2023)
This study aims to analyze the influence of Outdoor Education on improving students' self-confidence, particularly in the rational and realistic aspects. A quasi-experimental method with a Randomized Pretest-Posttest Comparison Group Design was employed. A total of 40 junior high school students were divided into experimental and control groups. The research instrument was a self-confidence questionnaire based on Lauster’s theory. The results showed that the experimental group experienced significant improvements in both aspects compared to the control group. Outdoor Education activities based on experiential learning proved effective in enhancing students' logical thinking, self-awareness, and realistic acceptance of their limitations. This study recommends the integration of Outdoor Education into school-based character education programs.